Analisis Gaya Belajar Siswa Berprestasi Studi Komparasi Siswa Berprestasi SMAN 1 dengan MAN 1 Yogyakarta Kelas XI - Ali Murfi; Noneng Siti Rosidah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
This study was conducted, first, analyzed to determine the learning styles of students excel in Mathematics and Science subjects in class XI SMAN 1 and MAN 1 Yogyakarta by applying the theory of David Kolb's learning style. Second, to predict the differences and similarities of learning styles of students achievement in learning Mathematics Class XI SMAN 1 and MAN 1 Yogyakarta. 18 research subjects were drawn from students of class XI. Determining the subject of research is done by using purposive sampling technique that refers to the result of the average value of UTS Mathematics which is the third highest of any class. The results showed that: (1). Students' learning styles achievement in Mathematics and Science subjects in class XI SMA N 1 and MAN 1 Yogyakarta is varied. This is evidenced by the results if the data obtained show that the student has a unique learning style of each and likely to lead to the individual's personality. Based on the analysis of student learning styles achievement shows that students SMA N 1 Yogyakarta been the subject of much research as 4 students have a learning style Assimilator, 3 students have learning styles Konverger, one student has a learning style Akomodator and one student has a learning style Diverger again. While students perform at MAN 1 Yogyakarta who is the subject of research, as many as four people have Akomodator learning styles, each two students have learning styles Assimilator and Diverger, then one student again has a learning style Konverger. (2). Differences in learning styles that happens is the individual habits that become unique to them. Students perform at SMA N 1 Yogyakarta dominates the Assimilator learning styles, while students of MAN 1 Yogyakarta dominates the Akomodator learning styles.